Metabolic Reprogramming in Gastric Cancer: Trojan Horse Effect - Bin, Yu-Ling; Hu, Hong-Sai; Tian, Feng; Wen, Zhen-Hua; Yang, Mei-Feng; Wu, Ben-Hua; Wang, Li-Sheng; Yao, Jun; Li, De-Feng (Frontiers in Oncology, 2022)
Worldwide, gastric cancer (GC) represents the fifth cancer for incidence, and the third as cause of death in developed countries. Despite the development of combination chemotherapies, the survival rates of patients with GC remain unsatisfactory. The reprogramming of energy metabolism is a hallmark of cancer, notably, an increased dependence on aerobic glycolysis. In this review, we examine the current evidence on how metabolic reprogramming in GC target tumor microenvironment, modulate metabolic networks, overcome drug resistance. Preclinical and clinical studies on the combination of metabolic reprogramming targeted agents with conventional chemotherapeutics or molecularly targeted treatments (including VEGFR, HER2) and the value of biomarkers is examined. Our deeper understanding of molecular mechanisms underlying successful pharmacological combinations is crucial to find the best personalized treatment regimens for cancer patients.